An Income to the Philosophical School of Master Javadi Amoli - میثم واثقی (حکمت اسرا, 2018)
The philosophical school of Professor Javadi Amoli follows Qom's sect and this sect define under Sadrai wisdom system. The present study try to present a phenomenological description of Ayatollah Javadi Amoli philosophical school. Such a description takes place from the examination of the various Manifestations of a thought to reveal the fundamental principle that has led to the fulfillment of the Manifestations. The present study is carried out by examining two philosophical Issues as a manifeste of Master Javadi Amoli's ideas. The first issue is the knowledge and will relation. The image of the knowledge and will relation in his thought is distinct from the image in Allameh Tabatabai's thought. While Allameh Tabatabai considers the knowledge of Must as intutive knowledge and the practical intellect as the source of it, for Ayatollah Javadi Amoli the knowledge of must is Propositional Knowledge which is below practical wisdom, and its exporter is theoretical intellect. The second witness is the references made by Master Javadi Amoli following the philosophy definition at the beginning of Asfar. In the thought of Master Javadi Amoli, philosophy is defined as definitive ontology; an Ontology, which includes conceptual recognition and argumental assertion of objects existence. What is being achieve by this description is that the monopoly of perception ability to theoretical intellect and the way in which practical intellect base on the theoretical intellect, is the foundation upon which his philosophical school is based. In this school, theoretical intellect and its levels, namely, empirical intellect, semi-abstract intellect, abstract intellect and pure intellect, have particular importance.